Sphingomonas chlorellae sp. nov., Isolated from Outdoor Photobioreactor Culturing Chlorella sp. HS2 with Soy Sauce Wastewater - Won-Suk Choi; So-Ra Ko; Yun-Kyoung Kwon; Hayoung Lee; Seonah Jeong; Hee-Sik Kim; Chi-Yong Ahn (Current Microbiology, 2026)

Growth inhibition of harmful cyanobacterium Microcystis by picocyanobacterium Cyanobium: transcriptome-based interaction analysis - Min-Seong Kim; So-Ra Ko; Mingyeong Kang; Seonah Jeong; Hayoung Lee; Yuna Shin; Kyunghyun Kim; Chi-Yong Ahn (Harmful Algae, 2025)

Ferrovibrio plantarum sp. nov., Isolated from the Co-culture of Myriophyllum spicatum (Water Milfoil) and Microcystis aeruginosa - Mingyeong Kang; Seonah Jeong; Ve Van Le; So-Ra Ko; Min-Seong Kim; Dong-Yun Choi; Chi-Yong Ahn (Current Microbiology, 2025)

Selective cyanobactericidal activity of Nocardioides convexus MS16 against Microcystis aeruginosa, mediated by direct attack - Seonah Jeong; Ve Van Le; So-Ra Ko; Mingyeong Kang; Min-Seong Kim; Zhun Li; Chi-Yong Ahn (Algal Research, 2025)

Algicidal effects of Fictibacillus sp. 5A8M on Margalefidinium polykrikoides through attachment and secretion of extracellular metabolites - So-Ra Ko; Ve Van Le; Sang-Ah Lee; Seung Ho Baek; Chi-Yong Ahn (Harmful Algae, 2025)

Roseateles microcysteis sp. nov., Isolated from Co-cultivation of Microcystis aeruginosa and Myriophyllum spicatum - Min-Seong Kim; Seonah Jeong; Mingyeong Kang; So-Ra Ko; Ve Van Le; Dong-Yun Choi; Chi-Yong Ahn (Current Microbiology, 2025)

Undibacterium cyanobacteriorum sp. nov., an auxin-producing bacterium isolated from fresh water during cyanobacterial bloom period - Ve Van Le; So-Ra Ko; Loan Thi Thanh Nguyen; Jin-Cheol Kim; Yuna Shin; Kyunghyun Kim; Chi-Yong Ahn (Antonie van Leeuwenhoek, 2024)

Microcystis abundance is predictable through ambient bacterial communities: A data-oriented approach - Mingyeong Kang; Dong-Kyun Kim; Ve Van Le; So-Ra Ko; Jay Jung Lee; In-Chan Choi; Yuna Shin; Kyunghyun Kim; Chi-Yong Ahn (Journal of Environmental Management, 2024)

Insights into cyanobacterial blooms through the lens of omics - Ve Van Le; Quynh-Giao Tran; So-Ra Ko; Hee-Mock Oh; Chi-Yong Ahn (Science of The Total Environment, 2024)

Succession of particle-attached and free-living bacterial communities in response to microalgal dynamics induced by the biological cyanocide paucibactin A - Ve Van Le; So-Ra Ko; Yuna Shin; Kyunghyun Kim; Chi-Yong Ahn (Chemosphere, 2024)

Effect of rainfall in shaping microbial community during Microcystis bloom in Nakdong River, Korea - Mingyeong Kang; Ve Van Le; So-Ra Ko; Seong-Jun Chun; Dong-Yun Choi; Yuna Shin; Kyunghyun Kim; Seung Ho Baek; Chi-Yong Ahn (Science of The Total Environment, 2024)

Dynamic response of bacterial communities to Microcystis blooms: A three-year study - Ve Van Le; Mingyeong Kang; So-Ra Ko; Seonah Jeong; Chan-Yeong Park; Jay Jung Lee; In-Chan Choi; Hee-Mock Oh; Chi-Yong Ahn (Science of The Total Environment, 2023)

Cultivation of Chlorella sp. HS2 using wastewater from soy sauce factory - Minsik Kim; Sang-Ah Lee; Jin-Ho Yun; So-Ra Ko; Dae-Hyun Cho; Hee Su Kim; Hee-Mock Oh; Hee-Sik Kim; Chi-Yong Ahn (Chemosphere, 2023)

Periphyton reduces cyanobacterial blooms by promoting potentially cyanobactericidal bacteria - Ve Van Le; So-Ra Ko; Mingyeong Kang; Yuna Shin; Byungjin Lim; Yoon-Ho Kang; Hee-Mock Oh; Chi-Yong Ahn (Journal of Applied Phycology, 2023)

Algicidal activity of a novel bacterium, Qipengyuania sp. 3-20A1M, against harmful Margalefidinium polykrikoides: Effects of its active compound - So-Ra Ko; Ve Van Le; Ankita Srivastava; Mingyeong Kang; Hee-Mock Oh; Chi-Yong Ahn (Marine Pollution Bulletin, 2023)

Effective control of harmful Microcystis blooms by paucibactin A, a novel macrocyclic tambjamine, isolated from Paucibacter aquatile DH15 - Ve Van Le; So-Ra Ko; Mingyeong Kang; Hee-Mock Oh; Chi-Yong Ahn (Journal of Cleaner Production, 2023)

Hymenobacter cyanobacteriorum sp. nov., isolated from a freshwater reservoir during the cyanobacterial bloom period - Ve Van Le; So-Ra Ko; Mingyeong Kang; Hee-Mock Oh; Chi-Yong Ahn (Archives of Microbiology, 2022)

Panacibacter microcysteis sp. nov., isolated from a eutrophic reservoir during the Microcystis bloom period - Ve Van Le; So-Ra Ko; Mingyeong Kang; Sang-Ah Lee; Hee-Mock Oh; Chi-Yong Ahn (Archives of Microbiology, 2022)

Elucidation of the Algicidal Mechanism of the Marine Bacterium Pseudoruegeria sp. M32A2M Against the Harmful Alga Alexandrium catenella Based on Time-Course Transcriptome Analysis - Suhyung Cho; Sang-Hyeok Cho; So-Ra Ko; Yujin Jeong; Eunju Lee; Sangrak Jin; Bo-Seong Jeong; Byung-Ha Oh; Hee-Mock Oh; Chi-Yong Ahn; Byung-Kwan Cho (Frontiers in Marine Science, 2021)
The marine dinoflagellate Alexandrium is associated with harmful algal blooms (HABs) worldwide, causing paralytic shellfish poisoning (PSP) in humans. We found that the marine bacterium Pseudoruegeria sp. M32A2M exhibits algicidal activity against Alexandrium catenella (Group I), inhibiting its motility and consequently inducing cell disruption after 24 h of co-culture. To understand the communication between the two organisms, we investigated the time-course cellular responses through genome-wide transcriptome analysis. Functional analysis of differentially expressed genes revealed that the core reactions of the photosystem in A. catenella were inhibited within 2 h, eventually downregulating the entire pathways of oxidative phosphorylation and carbon fixation, as well as associated metabolic pathways. Conversely, Pseudoruegeria upregulated its glycolysis, tricarboxylic acid cycle, and oxidative phosphorylation pathways. Also, the transporters for nutrients such as C3/C4 carbohydrates and peptides were highly upregulated, leading to the speculation that nutrients released by disrupted A. catenella cells affect the central metabolism of Pseudoruegeria . In addition, we analyzed the secondary metabolite-synthesizing clusters of Pseudoruegeria that were upregulated by co-culture, suggesting their potential roles in algicidal activity. Our time-course transcriptome analysis elucidates how A. catenella is affected by algicidal bacteria and how these bacteria obtain functional benefits through metabolic pathways.

Description of Hymenobacter daejeonensis sp. nov., isolated from grass soil, based on multilocus sequence analysis of the 16S rRNA gene, gyrB and tuf genes - Long Jin; Xuewen Wu; So-Ra Ko; Feng-Jie Jin; Taihua Li; Chi-Yong Ahn; Hee-Mock Oh; Hyung-Gwan Lee (Antonie van Leeuwenhoek, 2018)

Acidovorax lacteus sp. nov., isolated from a culture of a bloom-forming cyanobacterium (Microcystis sp.) - Seong-Jun Chun; Yingshun Cui; So-Ra Ko; Hyung-Gwan Lee; Ankita Srivastava; Hee-Mock Oh; Chi-Yong Ahn (Antonie van Leeuwenhoek, 2017)

Pusillimonas caeni sp. nov., isolated from a sludge sample of a biofilm reactor - Long Jin; So-Ra Ko; Yingshun Cui; Chang Soo Lee; Hee-Mock Oh; Chi-Yong Ahn; Hyung-Gwan Lee (Antonie van Leeuwenhoek, 2017)

Ferruginibacter profundus sp. nov., a novel member of the family Chitinophagaceae, isolated from freshwater sediment of a reservoir - Long Jin; Hyung-Gwan Lee; Hyun-Joon La; So-Ra Ko; Chi-Yong Ahn; Hee-Mock Oh (Antonie van Leeuwenhoek, 2014)